THE EFFECT OF PILATES EXERCISE TECNIQUE ON REDUCING THE INTENSITY OF PRIMARY DYSMENORHEA PAIN IN SMP NEGERI 05 BENGKULU CITY INDONESIA - Lusi Andriani; Windy Fitrianingsih; Suci Sholihat (Poltekkes Kemenkes Bengkulu, 2023)
The incidence of primary dysmenorrhea in Indonesia is around 54.89%, while the prevalence of primary dysmenorrhea in the city of Bengkulu in 2022 is the number of young women experiencing dysmenorrhea as many as 711 people (82%) out of 8,610 young female students. Young women who experience disruption in learning activities due to menstrual pain that is felt in the teaching and learning process causes young women to have difficulty concentrating because of the discomfort felt when menstrual pain This study aims to determine the effect of pilates exercise techniques on reducing the pain intensity of primary dysmenorrhea at SMP Negeri 05 Bengkulu city. This study used a quasi-experimental with a one group pretest-posttest. The population in this study was class VIII students at SMP Negeri 05 Bengkulu City with a sample of 34 people and for sampling in this study were students who experienced dysmenorrhea by means of purposive sampling and data analysis in the study using the Wilcoxon test. The results of this study found that the average dysmenorrhea pain before being given the pilates exercise technique was 5.74 and the average pain after being given the pilates exercise technique was 3,44. The Wilcoxon test results obtained p-value = 0.000 with a mean difference of 2,3 indicating that there is an effect of pilates exercise technique on reducing the intensity of primary dysmenorrhea pain at SMP Negeri 05 Bengkulu City in 2023. It is hoped that the school at SMP Negeri 05 Bengkulu City can provide information that the pilates exercise technique is an alternative therapy for dealing with young women who experience dysmenorrhea